Sentiment Analysis to Know Public Perception Regarding to Public Communication of Indonesian Customs and Excise - Nugroho, Baskoro Tri; Adi, Achwan Noorlistyo (Sinergi International Journal of Communication Sciences, 2024)
This study highlights the positive impact of social media sentiment analysis in enhancing public perception of the Directorate General of Customs and Excise in Indonesia. By employing the Social Media Analytics (SMA) framework and the Brand24 tool, the research examines public sentiment on Twitter and TikTok during two periods in 2024. The findings reveal a significant improvement in sentiment from May to mid-August, driven by the government's proactive and transparent communication, including direct intervention by the Minister of Finance. This shift underscores the effectiveness of responsive governance in fostering public trust and engagement. The study emphasizes the value of ongoing sentiment monitoring, proactive communication strategies, and the promotion of ethical standards as key to maintaining and further enhancing public confidence. These insights contribute positively to the understanding of social media’s role in public sector communication and its potential to support better governance.